Come into the Garden Room - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses creating a garden room or sunroom for one's home. Describes possible color schemes and decorative treatments for inspiration. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Garden rooms; Paint materials; Garden rooms--Design and construction; Garden rooms--Themes, motives; Varnish and varnishing; Interior decoration; Paint industry and trade; Advertising--Paint